BMP4 Upregulation Is Associated with Acquired Drug Resistance and Fatty Acid Metabolism in EGFR-Mutant Non-Small-Cell Lung Cancer Cells - Duc-Hiep Bach; Thi-; Donghwa Kim; Yong Jin An; Sunghyouk Park; Hyen Joo Park; Sang Kook Lee (Elsevier, 2018)
Lung cancer is the leading cause of cancer-associated deaths worldwide. In particular, non-small-cell lung cancer (NSCLC) cells harboring epidermal growth factor receptor (EGFR) mutations are associated with resistance development of EGFR tyrosine kinase inhibitor (EGFR-TKI) treatment. Recent findings suggest that bone morphogenetic proteins (BMPs) and microRNAs (miRNAs) might act as oncogenes or tumor suppressors in the tumor microenvironment. In this study, for the first time, we identified the potential roles of BMPs and miRNAs involved in EGFR-TKI resistance by analyzing datasets from a pair of parental cells and NSCLC cells with acquired EGFR-TKI resistance. BMP4 was observed to be significantly overexpressed in the EGFR-TKI-resistant cells, and its mechanism of action was strongly associated with the induction of cancer cell energy metabolism through the modulation of Acyl-CoA synthetase long-chain family member 4. In addition, miR-139-5p was observed to be significantly downregulated in the resistant NSCLC cells. The combination of miR-139-5p and yuanhuadine, a naturally derived antitumor agent, synergistically suppressed BMP4 expression in the resistant cells. We further confirmed that LDN-193189, a small molecule BMP receptor 1 inhibitor, effectively inhibited tumor growth in a xenograft nude mouse model implanted with the EFGR-TKI-resistant cells. These findings suggest a novel role of BMP4-mediated tumorigenesis in the progression of acquired drug resistance in EGFR-mutant NSCLC cells. Keywords: bone morphogenetic protein 4, miR-139-5p, EGFR-TKI resistance, Acyl-CoA synthetase long-chain family member 4, energy metabolism, EGFR-mutant NSCLC cells, p53, fatty acid, yuanhuadine